Nicotine Reduces Human Brain Microvascular Endothelial Cell Response to Escherichia coli K1 Infection by Inhibiting Autophagy - Wu, Chao; Yang, Mengzhen; Liu, Rui; Hu, Hanyang; Ji, Lulu; Zhang, Xiaoli; Huang, Shenghe; Wang, Lin (Frontiers in Cellular and Infection Microbiology, 2020)
Studies have shown that exposure to environmental tobacco smoke can increase the risk of bacterial meningitis, and nicotine is the core component of environmental tobacco smoke. Autophagy is an important way for host cells to eliminate invasive pathogens and resist infection. Escherichia coli K1 strain (E. coli K1) is the most common Gram-negative bacterial pathogen that causes neonatal meningitis. The mechanism of nicotine promoting E. coli K1 to invade human brain microvascular endothelial cells (HBMECs), the main component of the blood–brain barrier, is not clear yet. Our study found that the increase of HBMEC autophagy level during E. coli K1 infection could decrease the survival of intracellular bacteria, while nicotine exposure could inhibit the HBMEC autophagic response of E. coli K1 infection by activating the NF-kappa B and PI3K/Akt/mTOR pathway. We concluded that nicotine could inhibit HBMEC autophagy upon E. coli K1 infection and decrease the scavenging effect on E. coli K1, thus promoting the occurrence and development of neonatal meningitis.